Women's Writing from Wales before 1914 - Aaron, Jane (Historical Women's Writing, 2019)
This essay collection rediscovers and reassesses a host of still little-known, pre-1914, Welsh women writers. In the last few decades considerable advances have been made towards rediscovering, contextualising, and analysing women's writing from Wales. The combined influences of the post-1960s women's movement, the 1990s Welsh devolution successes, and the development of the 'Four Nations' school of British literary criticism, have together effected significant advances in the field of Welsh feminist literary studies. This book focuses in particular on: the fifteenth- to eighteenth-century Welsh-language bards, such as Gwerful Mechain, Angharad James, and Marged Dafydd; the seventeenth- and eighteenth-century English-language poets, including Katherine Philips, Jane Brereton, Anne Penny, and Anne Hughes; contributors to the Romantic movement in Wales, such as the poets and novelists Mary Robinson and Ann of Swansea; the mid-nineteenth-century protesting voice of polemicists such as Jane Williams (Ysgafell); the Victorian English-language novelists, for example Louisa Matilda Spooner, Anne Beale, Amy Dillwyn, Allen Raine, and Mallt Williams, and their concern with national, class, and gender identities; and early twentieth-century Welsh-language writers engaged with Welsh Home Rule and women's suffrage issues, such as Gwyneth Vaughan and Eluned Morgan.